Uso da sericina como protetor pulpar: uma revisão de literatura - Almeida , Ana Paula de (2019)
The use of silk sericin in tissue engineering in recent years is based on its antioxidant properties, antitumor effect, mitogenic effect on mammalian cells for example in the proliferation of keratinocytes and fibroblasts. In the search for new biomaterials, in the dental area sericin is included in order to investigate its use as a direct pulp capping agent, an endodontic procedure that requires the use of biocompatible materials with antimicrobial, anti-inflammatory, stimulating properties of sclerotic dentin and that provide protection to the pulp against thermoelectric and toxic stimuli. To date, calcium hydroxide (Ca (OH) 2) and mineral trioxide aggregate (MTA) are considered gold standard. For this purpose, the unpublished study by Hartman et al. (2018) showed that sericin has an anti-inflammatory effect throughout the treatment. In order to increase the knowledge about the application of sericin in pulp protections, the present work proposes to carry out a review of the literature consulting, from February to April, 2019, different databases. To date there is evidence that sericin induces proliferation of new cells, an important aspect for the success of direct pulpal capping